Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.envint.2014.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Airway oxidative stress and inflammation markers in exhaled breath from children are linked with exposure to black carbon

Abstract: BC exposure on the morning of sampling was associated with airway oxidative stress while 24-h and weekly exposures were linked with airway inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 55 publications
4
50
1
4
Order By: Relevance
“…Prior studies have found increased 8‐epi‐PGF 2α in exhaled breath condensate after exposure to air pollutants 22, 24, 25. However, systemic oxidative stress may be better reflected by 8‐epi‐PGF 2α measured in plasma or urine.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Prior studies have found increased 8‐epi‐PGF 2α in exhaled breath condensate after exposure to air pollutants 22, 24, 25. However, systemic oxidative stress may be better reflected by 8‐epi‐PGF 2α measured in plasma or urine.…”
Section: Discussionmentioning
confidence: 95%
“…The quantification of 8‐epi‐PGF 2α has been widely used as a noninvasive method to assess lipid peroxidation 20, 21. Higher short‐term air pollution has been associated with higher 8‐epi‐PGF 2α sampled from exhaled breath condensate in children, adolescents, and healthy young adults22, 23, 24, 25; however, few studies have assessed the relationship between exposure to ambient air pollution and urinary 8‐epi‐PGF 2α 26, 27 or in older populations at increased risk of cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…Different collectors, analysis methods and/ or sample processing procedures could explain these differences [9,[26][27][28]. IL-1β in EBC was of the same order of previous measurements in children in which EBC was sampled using the RTube™ and analysed in our lab [20].…”
Section: Discussionmentioning
confidence: 70%
“…Research on EBC has been done since several years, but there is still room to improve the method of sampling [15][16][17][18]. We sampled EBC via an optimized breath manoeuver [19] with the portable collection device RTube™ [20]. Using these state-of-theart methodologies the variability of inflammation markers within and between healthy individuals were determined to study their stability within one day and over a longer time period of twenty days.…”
Section: Introductionmentioning
confidence: 99%
“…At the experimental level, 2-h exposure to generated sulfate and soot particles was related to significant increases in FeNO in young and health subjects [13]. In children seen in two seasons, 24-h and weekly exposures to black carbon were linked with FeNO, while exposure on the morning of sampling was associated with airway oxidative stress [14], independently of sex, age, allergy status, parental education level and meteorological conditions on the sampling day.…”
Section: @Erspublicationsmentioning
confidence: 89%